Peek: Context Sharing on Request with Notifications - Brush, A.J.; Saponas, Scott; Ziola, Ryder; Smith, Greg; Johns, Paul; Roseway, Asta (CSCW '13 Proceedings of the 2013 conference on Computer supported cooperative work companion, 2013)
Ever wondered if it was a good time to call your spouse, child, or friend? Do you sometimes just want to know if they are on their way to meet you? With Peek you can request the activity state (e.g. walking, in vehicle, at-rest) and location of a phone when needed. Context is sent back automatically to people on the phone owner’s pre-approved Peek contact list. The person being peeked at receives a notification that provides awareness of who peeked at them and when.